Bangladeshi Migrant Workers’ Rights on the Front-lines of Covid-19 Epidemic: A Socio-legal Approach of Kafala System in Gulf Cooperation Council (GCC) Countries - Anowara, Fatema; Hossain, Mohammad Belayet (APPTHI, 2021)
The global shutdown resulting from the Covid-19 pandemic led the manpower industry to go through the toughest time in its history. As a result, Bangladeshi workers, on whom the wheel of the economy of Bangladesh is heavily dependent, are facing racism and systematic abuse of human rights across the Gulf Corporation Council (GCC) countries. Even prior to the pandemic, they were either exploited or not provided the working conditions and remunerations that they were promised. In this context, this study focuses to address the violation of human rights of migrant workers, including their families, due to the after-effect of Covid-19 epidemic and identifying the barriers they are facing in GCC countries. Using qualitative research method, this study will explore whether there is any legal solution for those migrant workers and their families and what sorts of rights need to be protected under National and International laws. In addition, this study will also focus on the responsibilities of their home and host states to fulfill them. Based on the findings, this study will provide various recommendations that could be considered by the Government of Bangladesh either by building skilled workers or by improving the enforcement of existing legislation or by bilateral investment treaties (BITs) with the Gulf State. Abstrak Shutdown global akibat pandemi Covid-19 membuat industri tenaga kerja mengalami masa terberat dalam sejarahnya. Akibatnya, pekerja Bangladesh, yang sangat bergantung pada roda ekonomi Bangladesh, menghadapi rasisme dan pelanggaran hak asasi manusia secara sistematis di seluruh negara Dewan Perusahaan Teluk (Gulf Corporation Council/GCC). Bahkan sebelum pandemi mereka dieksploitasi atau tidak diberikan kondisi kerja dan remunerasi yang dijanjikan. Dalam konteks ini, studi ini berfokus pada penanganan pelanggaran hak asasi pekerja migran termasuk keluarganya akibat dampak lanjutan dari epidemi Covid-19 dan untuk mengidentifikasi hambatan yang mereka hadapi di negara-negara GCC. Dengan menggunakan metode penelitian kualitatif, penelitian ini akan mengeksplorasi apakah ada solusi hukum bagi para pekerja migran dan keluarganya, dan hak-hak apa yang perlu dilindungi berdasarkan hukum Nasional dan Internasional. Selain itu, studi ini juga akan fokus pada tanggung jawab negara asal dan tuan rumah mereka untuk memenuhinya. Berdasarkan temuan tersebut, studi ini akan memberikan berbagai rekomendasi yang dapat dipertimbangkan oleh Pemerintah Bangladesh baik dengan membangun pekerja terampil atau dengan meningkatkan penegakan undang-undang yang ada atau dengan perjanjian investasi bilateral (bilateral investment treaties/BIT) dengan Negara Teluk. Kata kunci: Pekerja Migran, Covid-19, Migran Domestik atau Ilegal, Sistem Kafala, Pelanggaran Hak